2019
DOI: 10.14202/vetworld.2019.1395-1407
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment of the consumers living in Mount Lebanon directorate to antibiotics through medication and red meat intake: A cross-sectional study

Abstract: Background and Aim: The misuse and abuse of antibiotics by human and in animal production are leading to serious threats to global health. This study aimed to assess the dietary exposure of Lebanese consumers to antibiotic residues from the consumption of meat and compare it to that from medication intake. Materials and Methods: Beef samples (n=61) were collected and analyzed for penicillin residues using enzyme-linked immunosorbent assay and high-performance liquid chromatography. A cross-sectional study rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
7
2
Order By: Relevance
“…This difference is due to the fact that the quantity of beef consumed in Maroua is higher (134 g) with respect to that registered by these authors (38 g). The estimated dietary intake found in this study is also higher than that observed in Lebanon (9.6 μg/kg BW per day) by Bou-Mitri et al ( 19 ).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…This difference is due to the fact that the quantity of beef consumed in Maroua is higher (134 g) with respect to that registered by these authors (38 g). The estimated dietary intake found in this study is also higher than that observed in Lebanon (9.6 μg/kg BW per day) by Bou-Mitri et al ( 19 ).…”
Section: Discussioncontrasting
confidence: 76%
“…This difference is due to the fact that the quantity of beef consumed in Maroua is higher (134 g) with respect to that registered by these authors (38 g). The estimated dietary intake found in this study is also higher than that observed in Lebanon (9.6 µg/kg BW per day) by Bou-Mitri et al (19). From the analysis of data, it came out that, in Maroua, the daily intake of OTC residues per capita via beef consumption is 32.08 ± 8.08 µg (or 0.65 ± 0.16 mg/kg per day).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…For full control, several protocols must be implemented to educate consumer as well as farmers about the danger of brucellosis, about the fact that consuming raw milk is a route of infection, and about the importance of pasteurization and vaccination. Farmers and personnel should abide by Hazard Analysis and Critical Control Point practices to minimize the risk of infections that can be transmitted through direct contact, where these individuals are of high risk of spreading this disease [39,40]. They should also consider the necessary precautions in case of transportation or introduction of new animals to the farm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bacterial resistance genes derived from animal microbiomes may be horizontally transferred to human microbiota and to human pathogenic bacteria (Marshall & Levy, 2011 ). Exposure assessment can provide sufficient knowledge to eliminate or minimize human exposure to veterinary antimicrobial agents (Bou Mitri et al., 2019 ). Therefore, the monitoring of veterinary drug residues in animals and animal‐derived foods warrant particular attention.…”
Section: Introductionmentioning
confidence: 99%